The validity of diagnostic support of an asthma/COPD service in primary care - Lucas, Annelies (Oxford University Press, 2007)
BACKGROUND: To support GPs in diagnosing and monitoring their patients with asthma/chronic obstructive pulmonary disease (COPD), ‘asthma/COPD services’ have been developed. Within these services, pulmonologists perform structured diagnostic and therapeutic assessments based on the combination of written history data and spirometry. AIM: This study determines the validity of the diagnosis and advice when assessed using only written information. DESIGN OF STUDY: The results of the diagnostic procedures of an asthma/COPD service were compared with the results of regular office consultations by pulmonologists. SETTING: From January until August 2004, two pulmonologists examined 80 randomly selected patients referred to an asthma/COPD service in Eindhoven, the Netherlands. METHOD: Concordance was analysed between diagnosis and advice based on written spirometry and history data, with assessments based on live consultations with the same patients by pulmonologists. RESULTS: The validity of the assessed diagnosis was high (Cohen's κ = 0.82). When the diagnosis was uncertain, the advice for medical treatment scored low in validity (Cohen's κ = 0.39). The advice for additional diagnostic examinations had a high internal validity: in half of the patients, uncertainty in diagnosis turned into a definite diagnosis of asthma/COPD, or another cause for the complaints of the patient was revealed; in the other half, the diagnosis of asthma/COPD could be rejected. CONCLUSIONS: A structured asthma/COPD service offering diagnosis and diagnostic advice assessed from written spirometry and history data is a new and valid facility that can support the GP who faces the complicated diagnostic procedures in a progressive number of patients with asthma/COPD.